When Clerics Kill - Sani, Shehu (Book collections on Project MUSE., 2013)
The play depicts a troubled and violent society stoked by a vicious and violent culture of intolerance and extremism. It is about restiveness, puritanism and the politics of religiosity. The play gives a glimpse of the views and frustrations of young people, the supercilious and hateful perceptions of some clerics and the brigandage of law enforcers in such a given situation. The play points to the role courageous individuals could play in speaking out for peace and standing up to violence and in defiance of fear and for preservation of freedom.